2018
DOI: 10.22631/ijbmph.2018.55340
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiological study of toxoplasmosis in hemodialysis patients of Ahvaz, Southwest of Iran

Abstract: Introduction: Toxoplasma gondii (T. gondii) is an obligate intracellular protozoan that infects most warm-blooded vertebrates. Because of the immunodeficiency in hemodialysis patients, these individuals are at higher risk for reactivating chronic toxoplasmosis; therefore, a diagnosis of early and definitive in these individuals is highly desirable. Thus, the aim of this study is to investigate seroepidemiology of toxoplasmosis in hemodialysis patients of Ahvaz, southwest of Iran during 2015-2016. Methods: This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…When the immune system is compromised, acute or active infections, such as encephalitis, can lead to life-threatening complications. The study of Forough Kazemi, [20] , Al-Saadawi and Alkhaled [21] , Ayser and Abdul-Aziz [22] Bayani,M [23] ,Al-Dulaimi [24], Sharif Maraghi [25], recorded similar results of our current study. On the other hand, there are studies that differ with it Seyyedpour [26].…”
Section: Discussionsupporting
confidence: 89%
“…When the immune system is compromised, acute or active infections, such as encephalitis, can lead to life-threatening complications. The study of Forough Kazemi, [20] , Al-Saadawi and Alkhaled [21] , Ayser and Abdul-Aziz [22] Bayani,M [23] ,Al-Dulaimi [24], Sharif Maraghi [25], recorded similar results of our current study. On the other hand, there are studies that differ with it Seyyedpour [26].…”
Section: Discussionsupporting
confidence: 89%
“…Toxoplasma gondii (T. gondii) is a protozoan that results in a zoonotic disease known toxoplasmosis [1]. Sero-epidemiological studies have shown that the parasite antibodies are in serum of one-third of the world adult population [2]. The clinical signs of this disease lead to a substantial disease burden in humans worldwide, including ocular, cerebral, and congenital toxoplasmosis [1,3].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, this parasite can result in clinical manifestations in animal hosts of T. gondii, leading to lesser welfare for the affected hosts as well as major losses in livestock industry [1]. However, signs in people with healthy immune system are transient and mild which include swollen lymph and mild fever glands [2].…”
Section: Introductionmentioning
confidence: 99%